Construction of the Scale of child's attachment to his/her kindergarten teacher (CAKT) - Cugmas, Zlatka (Psihološka obzorja (Ljubljana), 2009)
In the theoretical part of this paper, the author gives answers to the question of whether a real attachment relationship can exist between a child and a non-maternal caretaker. She mentions the established methods of measuring the child's attachment to the kindergarten teacher. She presents The scale of child's attachment to his/her kindergarten teacher (CAKT), which is based on authors previous findings and the experience of other authors in the forming of psychological instruments of this type. The scale was tested in a research which involved twenty-five kindergarten teachers who participated in the evaluation of 178 children (49.4% boys). Children ranged in age from 3 to 6 years. The purpose of the study was to investigate the dimensionality and internal consistency of the Scale. It was established that the psychometric characteristics of the Scale were adequate. This paper also presents the limitations of the research, which should be considered in the interpretation of the obtained results. Replication studies using clinical groups and samples from different cultures will be needed to assess a possible generalization of the presented results.
Keywords: attachment theory; navezanost; predšolski otroci; vzgojiteljice; socialno vedenje; ocenjevalne lestvice; merjenje